Redesign the Wood Cutting Saw to Be More Ergonomic Using The TRIZ Method - Rizky Ravsanjani; Fakhrur Raji; Manda Salahuddin (Lembaga Penelitian dan Ilmu Pengetahuan JEPIP, 2023)
A cutting saw is one of the tools used to cut wood material. In this regard, the cutting saw still has shortcomings in its application. Several testing methods were conducted to analyze the failures of cutting saws circulating in the community, including the Nordic body map questionnaire. After checking directly, there are complaints of pain when using a cutting saw, especially on the right hand. For this reason, it is necessary to redesign it as a consideration later expected to improve the shortcomings in the current cutting saw. Several methods are used in this redesign, including TRIZ, OWAS, and anthropometry. TRIZ is a method used in the development of a design. This method's concept leads to solutions to the problem of contradictions that occur and leads to innovative solutions that have been tested with 100% success. After obtaining the function or attributes of the product, the next stage is to improve the user's posture so that the cutting saw tool can be used optimally and can initiate. The OWAS method corrects the postural position used in cutting saws. The specification of the handsaw product design based on the processing of the voice of the customer using a tree analysis diagram is that the features are reducing fatigue levels and being able to cut quickly, as well as for reliability, namely the handle with anti-slip qualities.